Features of the world market of raw materials - Safarova, A. S. (ТДАТУ, 2020)
The pricing model, on the basis of which the forecast on world energy markets is formed, is as follows: growth or decrease in growth rates and, accordingly, production volumes of the world economy causes increase or decrease in demand for fossil fuels, it stimulates demand for turn affects the dynamics of prices.
Keywords: the world market of oil products have; pricing model; independent networks for trade in petroleum